Global meta‐analysis of native and nonindigenous trophic traits in aquatic ecosystems. (26th October 2016) - McKnight, Ella; García‐Berthou, Emili; Srean, Pao; Rius, Marc
Abstract: Ecologists have recently devoted their attention to the study of species traits and their role in the establishment and spread of nonindigenous species (NIS). However, research efforts have mostly focused on studies of terrestrial taxa, with lesser attention being dedicated to aquatic species. Aquatic habitats comprise of interconnected waterways, as well as exclusive introduction vectors that allow unparalleled artificial transport of species and their propagules. Consequently, species traits that commonly facilitate biological invasions in terrestrial systems may not be as represented in aquatic environments. We provide a global meta‐analysis of studies conducted in both marine and freshwater habitats. We selected studies that conducted experiments with native and NIS under common environmental conditions to allow detailed comparisons among species traits. In addition, we explored whether different factors such as species relatedness, functional feeding groups, latitude, climate, and experimental conditions could be linked to predictive traits. Our results show that species with traits that enhance consumption and growth have a substantially increased probability of establishing and spreading when entering novel ecosystems. Moreover, traits associated with predatory avoidance were more prevalent in NIS and therefore favour invasive species in aquatic habitats. When we analysed NIS interacting with taxonomically distinctive native taxa, we found that consumption and growth were particularly important traits. This suggests that particular attention should be paid to newly introduced species for which there are no close relatives in the local biota. Finally, we found a bias towards studies conducted in temperate regions, and thus, more studies in other climatic regions are needed. We conclude that studies aiming at predicting future range shifts should consider trophic traits of aquatic NIS as these traits are indicative of multiple interacting mechanisms involved in promoting species invasions.